Bissu as Trustees of Bugis Tribe - Juniawan Mandala Putra; Vivi Novribe; Menorizah (PT FORMOSA CENDEKIA GLOBAL, 2023)
The most important role of all existing customs such as the custom of moving houses, marriages, births, circumcision, hataman quran is inseparable from the figure of bissu from the Bugis tribe where they are the last defense of the custom of the Bugis tribe who can translate every detail of the customs that must be used in At every event, this bissu can also be said to be someone who has knowledge in dictating each series of events, this bissu is the embodiment of a man who becomes a female figure who is often called celebai, transgender and their types, but the level of this bissu has already existed during the work of Goa. the duty of a bissu was as a royal adviser who was highly respected at that time. In this study the method used was a literature review using a descriptive approach and the results of direct interviews with the research object consisting of 6 prospective bissu and 5 bissu who have been bissu for almost 30 years as well as empirical data that supports phenomena in the field. . The tradition of the Bugis tribe or what is usually called to ogi has a very long series, but the one who can know the sequence is a group that is sacred, namely bissu who knows the sequence of what the Bugis tribe must do in the event, why is it like that because from the era of the formation of the kingdom Goa Bissu is the work's right hand and he also knows the sequence of what is being done at work and can explain to the surrounding community what must be done while they are the Bugis tribe until now.